1991
DOI: 10.1111/j.1365-2826.1991.tb00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Exerts Site‐, Context‐ and Dose‐Dependent Effects on Agonistic Responding in Hamsters

Abstract: Site-, context-and dose-dependent actions of intrahypothalamic cortisol administration on the agonistic behaviors of adult male golden hamsters (n = 128 dyads) were examined. W h e n cortisol-treated animals were tested in paired encounters with aggressive cholesterol-treated opponents, chronic ( 2 2 4 h ) cortisol treatment (1 mm implants) induced significant (P < 0.05) submission in three medial hypothalamic a r e a s (anterior hypothalamic area > medial preoptic area > ventromedial hypothalamus), but aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 56 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…It could be that the association of the history of CORT secretion as measured through CORT metabolites with territorial behavior registered 5 days later may have arisen due to a direct role of CORT on the promotion of aggressive behavior. In fact, studies in mammals have shown that glucocorticoids may have a direct regulatory role on the promotion of aggressive behaviors (Hayden-Hixson and Ferris 1991;Haller et al 1997;Mikics et al 2004Mikics et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that the association of the history of CORT secretion as measured through CORT metabolites with territorial behavior registered 5 days later may have arisen due to a direct role of CORT on the promotion of aggressive behavior. In fact, studies in mammals have shown that glucocorticoids may have a direct regulatory role on the promotion of aggressive behaviors (Hayden-Hixson and Ferris 1991;Haller et al 1997;Mikics et al 2004Mikics et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that territorial aggression in birds causes a rapid increase in CORT levels, suggesting that this hormone may play a specific role in the regulation of territorial behavior (Landys et al 2007). In fact, studies on rodents indicate that glucocorticoids may act directly on the facilitation of aggressive behaviors (Hayden-Hixson and Ferris 1991;Haller et al 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Studies in mammals showed that injections of ACTH and related peptides can alter forms of avoidance 20 40 41 , stretching and yawning 42 , grooming 43 and sexually motivated actions 44 ; thus a role for pituitary peptides in regulating arousal has been suggested 45 . Evidence also shows that glucocorticoid administration can influence locomotion 22 46 , agonistic reactions 47 48 49 and courtship 23 50 51 . These studies relied on injections of exogenous hormones and behavioural measures of varying delays; rapid effects of endogenous effectors from the pituitary–adrenal unit have not been documented before.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other reports of increased corticosterone secretion following social encounters (File and Seth, 2003). While elevated corticosterone levels often correlate with aggression in rodents (Hayden-Hixson and Ferris, 1991) and humans (van Bokhoven et al, 2005), this relationship is complicated and the literature is not entirely in agreement (Summers and Winberg, 2006). This heterogeneity may represent inherent individual differences in emotionality, risk-taking, and impulsivity.…”
Section: Discussionmentioning
confidence: 99%